Uma Saami Native Harvest Data Derived from Royal Swedish Taxation Records 1557-1614 - Wheelersburg, Robert P. (ARCTIC, 1991)
Royal tax records from 1557 to 1614 provide native harvest data for descriptive and quantitative analysis of the Saami (Lapp) reindeer hunting society in northern Sweden. The Saami made tax payments during the Scandinavian Late Middle Ages to Crown sheriffs in natural harvest products according to standardized equivalents. These natural goods were obtained in three areas of subsistence - hunting/trapping, fishing, and primitive reindeer husbandry, allowing for a graphic depiction of the economic performance of extended Saami families during this period prior to the adoption of modern reindeer herding. The native harvest, combine with enthnohistorical information, provides a model for reconstructing traditional circumpolar economies.Key words: Saami (Lapps), hunting economy, reindeer, taxation, Sweden, native harvest Mots clés: Samits (Lapons), économie de la chasse, renne, redevances, Suède, récoltes autochtones